Frequent Occurrence of p53 Gene Mutations in Uterine Cancers at Advanced Clinical Stage and with Aggressive Histological Phenotypes - Tsuda, Hitoshi (Jpn J Cancer Res, 1992)
The clinical and pathological significance of mutation of the p53 tumor‐suppressor gene was examined in 108 cases of primary uterine cancers using single‐strand conformation polymorphism and direct DNA sequencing analyses. Mutation of the p53 gene was detected in 19 (31%) of 62 cases of cancer of the uterine corpus and was more frequent in groups at an advanced clinical stage and/or with aggressive histology. Among four adenocarcinomas arising in the lowest portion of the uterine corpus, three showed integration of human papillomavirus (HPV) types 16 and/or 18 DNA, and two of them also showed p53 mutation. In cancer of the uterine cervix, p53 mutations were rare; 1% (3/46) in total, 3% (1/30) of cases with integration of HPV types 16 and/or 18 DNA and 13% (2/16) of cases without HPV DNA integration. Three mutations were detected among two cases at clinical stage IV and two cases of undifferentiated cervical carcinoma. Immunohistochemically, all five cases of uterine cancer which showed diffuse (>50% of cancer cells) nuclear staining of p53 protein also carried the p53 mutation. Therefore, p53 alterations were suggested to be involved in the development of uterine cancers showing aggressive biological behavior. Although a high incidence of HPV DNA integration and a low incidence of pS3 mutation were confirmed in cancer of the uterine cervix, there was no inverse association between integration of HPV types 16 and/or 18 DNA and p53 mutation.